Oral health behaviors in a sample of Portuguese adolescents: an educational issue - Veiga, Nélio J. (2014)
BACKGROUND: The objective of this study was to determine the prevalence of oral health behaviors among a sample of Portuguese adolescents and to evaluate the association with socio-demographic factors. METHODS: This cross-sectional study was conducted among 447 adolescents aged 12-19 years, attending a public school in Sátão, Portugal. A self-administered questionnaire was applied for data collection. RESULTS: The prevalence of tooth brushing (twice-a-day or more) was 90.6%. About 6% of adolescents reported daily flossing, which was more frequent among female gender (female, OR=2.03, 95%CI= (1.35 to 3.05)) and adolescents older than 15 years (>15years, OR=1.90, 95%CI= (1.24 to 2.92)). Sixty-seven percent had at least one dental appointment in the previous twelve months. The prevalence of dental appointments was associated with the father´s professional situation (unemployed, OR=0.33, 95% CI= (0.17 to 0.65)) and crowding index (>1, OR=0.4, 95%CI=(0.16 to 0.98)). Thirty-two point nine percent of adolescents referred having at least one episode of dental pain during their lives.CONCLUSION: The results highlight the need for improvement of oral health community programs and primary preventive strategies to reduce the risk of oral diseases and develop better oral health behaviours.